CD 123 - Wheat bread for white flour in cool regions of Brazil - Marchioro,Volmir Sergio (2014)
Cultivar CD 123 is recommendable for the wheat-growing regions 1, 2 and 3 of the States of Rio Grande do Sul, Santa Catarina and Paraná. It is a white flour wheat destined for production in cooler regions. The mean potential yield is 3514 kg ha-1, exceeding that of the control cultivars by 5%.